Meta-Analysis: Hypnotherapy and Its Effect on Quitting Smoking Behavior - Jihan Nafisah Fauziyyah; Hanung Prasetya; Bhisma Murti (Journal of Health Promotion and Behavior, 2022)
Background: Smoking is still a major health problem, about 23% of the world's population smokes. Indonesia is in the 3rd rank with the number of active smokers worldwide and more than 97 million Indonesians are exposed to cigarette smoke. Hypnotherapy can play a role in controlling smoking habits with a psychological health approach that is used to change human behavior and habits. The purpose of this study was to analyze the effect of hypnotherapy on the success of smoking cessation in active smokers based on the results of previous similar studies.Subjects and Method: This study was a meta-analysis with the following PICO, Population: active adult smokers. Intervention: hypnotherapy. Comparison: no hypnotherapy. Result: decreased pain. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. The keywords to search for articles are “hypnotherapy” OR “hypnosis” AND tobacco OR smoke OR smoked OR smoker AND “smoking cessation”. The articles included are English and Indonesian full text with a randomized control trial study design from 2008-2022. Article selection is done by using PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 9 Randomized Controlled Trial studies from the continents of Europe, America, Asia and Africa were selected for systematic review and meta-analysis. It was found that hypnotherapy can increase the success of smoking cessation and is statistically significant (SMD= 1.32; CI 95% = 0.53 to 2.12; p=0.001).Conclusion: Hypnotherapy increases the success of smoking cessation in active adult smokers.Keywords: hypnoterapy, hypnosis, tobacco, smoker, smoking cessation.Correspondence: Jihan Nafisah Fauziyyah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: jihannafisah321@gmail.com. Mobile: +6289611006503.Journal of Health Promotion and Behavior (2022), 07(04): 273-283DOI: https://doi.org/10.26911/thejhpb.2022.07.04.01